(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
The purpose of this study was to demonstrate how an anti-parasitic drug can be obtained from an aqueous extract that was taken from the leaves of Coriandrum sativum and used to test the viability of Toxoplasma gondii. In this study, a total of 20 male rats were used, divided into the following four groups (with each group containing four rats): The normal saline was administered to the rat in the oral route. T. gondii tissue cysts were administered intraperitoneally into a rat in a volume of one milliliter containing one hundred tissue cysts. The extract of Coraindrium sativum was given to the rat every day via oral administration at a dose of 250 mg/kg body weight. A rat was given an intraperitoneal injection of 1 milliliter of T. gondii tissue cysts and then given an extract of leaves at a dosage of 250 milligrams per kilogram of body weight each day for a period of 30 days. When compared with control rats, the study’s findings showed a substantial (P